2016
DOI: 10.3928/23258160-20160229-03
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Retinal Perfusion Resulting From Vitreoretinal Traction: A Mechanism of Retinal Vascular Insufficiency

Abstract: The authors demonstrate that vitreoretinal traction can alter retinal vascular perfusion in a reversible fashion. These results suggest that there can be a direct mechanical effect of vitreous traction on retinal vascular perfusion. Further advances in wide-field imaging, wide-field OCT, and OCTA will help better evaluate this cause of retinal vascular insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The post-ocriplasmin VMT release (complete or incomplete) might justify the observed tissue relaxation, together with microvascular density reduction. This hypothesis might consolidate the findings made by Kashani [11], and Mastropasqua [8].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The post-ocriplasmin VMT release (complete or incomplete) might justify the observed tissue relaxation, together with microvascular density reduction. This hypothesis might consolidate the findings made by Kashani [11], and Mastropasqua [8].…”
Section: Discussionsupporting
confidence: 90%
“…The rationale of our study was to investigate possible microvascular alterations in VMT, and to observe changes after intravitreal ocriplasmin injection. Kashani et al used fluorescein angiography to show microvascular pattern alterations produced by vitreoretinal traction, and also demonstrated their reversibility, suggesting a possible direct mechanical effect of vitreous traction on retinal perfusion [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following were analyzed as potential confounders: presence of vitreomacular traction [ 18 ], epiretinal membrane(H. [ 19 ]), macular hole [ 20 ], myopia [ 21 ], previous vitreoretinal surgery [ 22 ], diabetes [ 23 ], systemic arterial hypertension [ 24 ], cognitive impairment [ 25 ], previous stroke [ 26 ], chronic kidney disease [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…In one study, Pierro et al [19] proposed the hypothesis that tangential traction could cause vasodilation and congestion in the formation of macular hole. It has also been reported that vitreous retinal traction can cause reversible changes in retinal vascular perfusion, indicating that vitreous traction has direct force on retinal vessels [20] . Therefore, we believe that in the process of MH, the number and total area of cysts in the OPL+HFL complex continue to increase, which produces certain tension to the SCP of the retina and changes the structure of the capillaries located in the layer of ganglia cells and nerve bers, which may cause the congestion of blood vessels, and then cause the change of vascular density.…”
Section: Discussionmentioning
confidence: 95%